Preparation, preliminary characterization and mechanical properties of epoxy composites reinforced with spent coffee grounds - Tarazona, E. R. T.; Oliveira, L. S.; Rubio, J. C.; Franca, A. S. (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
The use of bio-based materials for production of biocomposites is of interest due to their low cost, abundance and the fact that they are renewable and biodegradable. In this work, an epoxy matrix was produced from residual soybean oil and subsequently used in the preparation of composites reinforced with spent coffee grounds (SCG) fiber. SCG were chemically treated with alkaline hydrogen peroxide in order to decrease hydrophilicity and increase interfacial interaction of polymeric composites. The effects of variations in the molar ratio of maleic anhydride (curing agent) and in the SCG mass fraction were compared in terms of tensile strength and elastic modulus as well as physical parameters (bulk density, apparent porosity and water absorption). The results obtained indicated that it was possible to produce an epoxy matrix from the residual soybean oil and to use it as polymeric material in the production of biocomposites reinforced with treated spent coffee ground. The composites prepared with a molar ratio of maleic anhydride 1: 1.2 and SCG mass fraction of 35% were those that presented the best mechanical properties.